Packed‐Column of Granular Activated Carbons for Removal of Chemical Oxygen Demand from Industrial Wastewater. Issue 3 (13th December 2012) - Laohaprapanon, Sawanya; Marques, Marcia; Kaczala, Fabio; Hogland, William
Abstract In the present study, chemical oxygen demand (COD) removal by packed‐columns of activated carbon (AC) derived from two different materials (coal activated carbon, CAC and wood activated carbon, WAC) is reported as part of an on‐site wastewater treatment system for handling small volumes of wastewater generated at wood‐floor industries for which there are no proper on‐site treatment options available in the market. The performance of the sorbents, the effect of bed depth (0.19 and 0.57 m) and volumetric load (0.10 and 0.24 m h−1) on the breakthrough curve of sorption systems were studied. The results indicated the feasibility of using both ACs to treat these wastewaters. At the bed depth (0.57 m), volumetric load (0.24 m h−1), and 30% breakthrough, CAC and WAC showed treatment capacity of 40.5 L kg−1 in 250 h and 23.8 L kg−1 in 63 h, respectively. This indicated that CAC requires longer retention times to reach a performance similar to WAC. The experimental data was fit into the bed depth‐service time model showing that under the same conditions, CAC had higher maximum sorption capacity (N0) than WAC. Moreover, thermal regeneration at 500°C temperature could be a cost‐effective procedure since the reuse of spent AC through such regeneration process for further treatment could still achieve 90% of the initial sorption capacity, reducing then costs for the use of new sorbents and also the need for waste disposal.